Problematika Transliterasi Aksara Arab-Latin: Studi Kasus Buku Panduan Manasik Haji dan Umrah - Nur Fauzan Ahmad (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Society needs transliteration of Arabic script to Latin script to help those who can not read Arabic letter correctly. Reality shows there are many problems in the business. Although there is a Joint Decree between the Minister of Education and the Minister of Religious Affairs on Arab-Latin Transliteration Guidance, but in fact there are many versions of transliterations in the field. This paper discusses the problematics of Arab-Latin transliteration in Indonesian, with case studies on the Panduan Hajj and Umrah books of the Ministry of Religious Affairs, Travel Haji and Umroh PT Razek and Zidni Silma and Jamiatul Hujaj Kudus. The version of PT Razek follows the Transliteration guidelines of the two ministers, but still causes a lot of mispronunciations which result in misrepresentation. Books published by JHK Kudus attempt to bridge the difficulties faced by some Javanese Islamic community by creating their own transliteration system. Transliteration is quite helpful. It seems necessary to re-agree Latin Arabic transliteration system by considering the principle of the truth of speech and habits that exist in the community